Breaking Stereotypes: Authority Challenges and Management Strategies for Women Leaders in the Workplace - Zhang, Ziwei (International Journal of Global Economics and Management, 2024)
As global gender equality awareness grows, women are increasingly influential across fields, especially in leadership. Yet, female managers still face many dilemmas rooted in ingrained gender roles, intertwined with power structures, work-family balance, and gender biases. This paper analyzes academic literature and successful female leaders to uncover workplace troubles and explore social-cultural motivations. The research shows that factors like superior communication, strong self-identity, extensive networks, and institutional support are both advantages and disadvantages for female leaders. The study advocates for a holistic social response to create a fairer work environment, empowering women leaders to unleash their potential and contribute to progress. It provides insights for current and aspiring female leaders and opens new perspectives for theoretical and practical exploration, ultimately aiming to promote gender equality in the workplace and beyond.